Annotated Code of the State of Iowa Containing All the Laws of a General Nature Enacted by The Twenty-Sixth General Assembly at the Extra Session, Which Adjourned July 2, 1897 Page 1955 (Vol. 1, 1897) § 5004 - (:unkn) unknown (General Publisher, 1897)
Prohibited selling, presenting, or giving, any pistol, revolver, or toy pistol to any minor. Violators fined not less than twenty-five nor more than one hundred dollars, or imprisoned not less than ten nor more than thirty days in jail.
--
Keywords: TRANSFER - MINORS